Rethinking Indonesia's Welfare State: A Legal Comparative Study of the Constitutional Court's Decision 64/PUU-XVIII/2020 with South Korea Practice - Suryawan, Dhian Fajar (Sultan Jurisprudence: Jurnal Riset Ilmu Hukum, 2025)
The founding fathers of Indonesia established a constitutional mandate for a welfare state, requiring the government to control and manage vital resources for the people’s collective prosperity. This principle, codified in Article 33 of the 1945 Constitution, is increasingly relevant amid ongoing debates about economic justice and resource management. The Constitutional Court's decision in Case No. 64/PUU-XVIII/2020 ruled that recent amendments to the Mineral and Coal Mining Law deviate from this constitutional vision, sparking a critical legal and political discussion. This research provides a timely analysis of this landmark decision, highlighting its significant implications for the future of Indonesia’s welfare state. Our contribution is an urgent call for policymakers and legal scholars to re-evaluate the foundational principles guiding national economic policy.